The Development of GABAergic Network in Depression in Recent 17 Years: A Visual Analysis Based on CiteSpace and VOSviewer - Lin, Jieping; Ling, Fa; Huang, Ping; Chen, Min; Song, Min; Lu, Kangrong; Wang, Wanshan (Frontiers in Psychiatry, 2022)
In this study, we analysed the status and research trends of the GABAergic system in depression from 2004 to 2020 to provide a reference for further research. The Web of Science database was used as the data source and 1658 publishments were included. Using two visualisation analysis software, CiteSpace and VOSviewer, we analysed the publishing years, countries, institutions, authors, journals, categories, keywords, and research frontiers in depression. The publishments revealed an upward trend from 2004 to 2020; the most prolific country and institutions were the United States and INSERM, respectively. The journal of Neuroscience was the most published and cited journal. The most relevant category was neurosciences. The hot topics in this field were GABAergic research in Gaba(a) receptor; the research frontier was depressive model. These analysis results provide a new perspective for researchers to conduct studies on related topics in the future and guidance for scientists to identify potential collaborators and research cooperation institutions.